Lineage-Specific Analysis of Syk Function in Autoantibody-Induced Arthritis - Németh, Tamás; Futosi, Krisztina; Szilveszter, Kata; Vilinovszki, Olivér; Kiss-Pápai, Levente; Mócsai, Attila (Frontiers in Immunology, 2018)
Autoantibody production and autoantibody-mediated inflammation are hallmarks of a number of autoimmune diseases. The K/B×N serum-transfer arthritis is one of the most widely used models of the effector phase of autoantibody-induced pathology. Several hematopoietic lineages including neutrophils, platelets and mast cells have been proposed to contribute to inflammation and tissue damage in this model. We have previously shown that the Syk tyrosine kinase is critically involved in the development in K/B×N serum-transfer arthritis and bone marrow chimeric experiments indicated that Syk is likely involved in one or more hematopoietic lineages during the disease course. The aim of the present study was to further define the lineage(s) in which Syk expression is required for autoantibody-induced arthritis. To this end, K/B×N serum-transfer arthritis was tested in conditional mutant mice in which Syk was deleted in a lineage-specific manner from neutrophils, platelets or mast cells. Combination of the MRP8-Cre, PF4-Cre or Mcpt5-Cre transgene with floxed Syk alleles allowed efficient and selective deletion of Syk from neutrophils, platelets or mast cells, respectively. This has also been confirmed by defective Syk-dependent in vitro functional responses of the respective cell types. In vivo studies revealed nearly complete defect of the development of K/B×N serum-transfer arthritis upon neutrophil-specific deletion of Syk. In contrast, Syk deletion from platelets or mast cells did not affect the development of K/B×N serum-transfer arthritis. Or results indicate that autoantibody-induced arthritis requires Syk expression in neutrophils, whereas, contrary to prior assumptions, Syk expression in platelets or mast cells is dispensable for disease development in this model.